PENGARUH PENERAPAN METODE CHAIN WRITING TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS VIII SMPN 27 MAKASSAR - Nur Afni; Azis; Asis Nojeng (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Short story writing is one of the essential competencies in Indonesian language learning because it fosters students' creativity, critical thinking, and language skills. However, the teaching of short story writing in schools still faces several challenges, including students' limited ability to develop ideas, organize plots, and apply appropriate language conventions. This study aimed to describe students' short story writing skills before and after the implementation of the chain writing method and to examine its effect on the short story writing skills of eighth-grade students at SMP Negeri 27 Makassar. This research employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The sample consisted of 30 students selected from a population of 366 eighth-grade students. Data were collected through a short story writing test and classroom observations and were analyzed using descriptive and inferential statistics. The results revealed that the mean pretest score was 45.30, which fell into the less skilled category, while the mean posttest score increased to 79.20, categorized as skilled. The hypothesis testing showed an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05), indicating that the alternative hypothesis was accepted. Therefore, the implementation of the chain writing method had a significant effect on the short story writing skills of eighth-grade students at SMP Negeri 27 Makassar. These findings suggest that the chain writing method can serve as an effective collaborative learning strategy to improve students' short story writing skills.